Characterizing the Structural Integrity of Endotracheal Tube Taping Techniques: A Simulation Study. (August 2020) - Matchett, Gerald; Yang, Judy H.; Sripathi, Nishith R.; Simpkins, Landon; Ruikar, Kinnari; Minhajuddin, Abu; Whitten, Charles W.
Abstract : BACKGROUND: Endotracheal tubes (ETTs) are commonly secured with tape to prevent undesirable tube migration. Many methods of taping have been described, although little has been published comparing various methods of taping to one another. In this study, we evaluated several methods for securing ETTs with tape. We hypothesized a difference in mean peak forces between the methods studied during forced extubation. METHODS: Five methods of securing an ETT with tape were studied in a variety of contexts including cadaver and simulation lab settings. Testing included measurement of peak force (Newton [N]) during forced extubation, durability of taping following mechanical stress, effects of tape length–width variation, and characterization of failure mechanisms. RESULTS: We found several significant differences in mean peak extubation forces between the 5 methods of taping, with mean peak forces during forced extubation ranging from 20 N to 156 N. In separate tests, we found an association between mean peak forces and total surface area as well as geometric configuration of tape on the face. Long thin strips of tape appeared to provide surprising durability against forced extubation, a phenomenon that was associated with minimization of the "peel angle" as tape was removed. CONCLUSIONS: We found evidence of differential structural integrity between the 5 taping methods studied. More generally, we found that increased peak extubation forces were associated with increased total surface area of tape and that minimization of the "peel angle" by lateral application of tape is associated with surprisingly high relative peak extubation forces.